Silicon-hydroxyapatite bioactive coatings (Si-HA) from diatomaceous earth and SiO2: study of adhesion and proliferation of osteoblast-like cells - López-Álvarez, M. (2008)
The aim of this study consisted of investigating the influence of bioactive ceramic coatings of silicon substituted hydroxyapatite (Si-HA) over the behaviour of the human osteoblast-like cell (SaOS-2) line. Pulsed laser deposition (PLD) was the selected technique to deposit the coatings over titanium substrates. Diatomaceous earth and SiO2, together with commercial hydroxyapatite were respectively the silicon and HA sources used to produce the Si-HA coatings. HA coatings with 0% of silicon were used as control of the experiment. [...]